Serine in plants: biosynthesis, metabolism, and functions - Ros, R.; Muñoz-Bertomeu, J.; Krueger, S.
Serine (Ser)has a fundamental role in metabolism and signaling in living organisms. In plants, the existence of different pathways of Ser biosynthesis has complicated our understanding of this amino acid homeostasis. The photorespiratory glycolate pathway has been considered to be of major importance, whereas the nonphotorespiratory phosphorylated pathway has been relatively neglected. Recent advances indicate that the phosphorylated pathway has an important function in plant metabolism and development. Plants deficient in this pathway display developmental defects in embryos, male gametophytes, and roots. We propose that the phosphorylated pathway is more important than was initially thought because it is the only Ser source for specific cell types involved in developmental events. Here, we discuss its importance as a link between metabolism and development in plants.
Keywords: PHOSPHORYLATED SERINE BIOSYNTHESIS PATHWAY; PLANTS; SERINE BIOSYNTHESIS